Inuit Case and Agreement - Vincent van Gerven Oei (2005)
Section 2 will focus on the case patterns of simple Inuit transitive clauses. Section 3 deals with the Inuit ‘ergative’ agreement system. Section 4 addresses the Inuit phrase structure typology. Section 5 deals with the Inuit case system into more depth.